1960
DOI: 10.1139/v60-159
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxide Films on Niobium: Thickness, Dielectric Constant, Dispersion, Reflection Minima, Formation Field Strength, and Surface Area

Abstract: The wavelengths of minimum specular reflectivity (at 11' incidence) due to interference were determined using a spectrophotometer for a series of films formed on chemically polished niobium. With a value of the refractive index n = 2 . 4 6 f 1% a t 4358 A wavelength by the Abelhs method (reported elsewhere), the spectrophotometric data give the refractive index as a function of the wavelength X, 11 = 2.26+0.398/(X/103 A-2.56)l.~. T o analyze the spectrophotometric results, an auxiliary measure of thickness was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1962
1962
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…Manuscript received Nov. 29,1964. This paper was presented in part at the Pittsburgh Meeting, April 15-18, 1963.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript received Nov. 29,1964. This paper was presented in part at the Pittsburgh Meeting, April 15-18, 1963.…”
Section: Discussionmentioning
confidence: 99%
“…While these values are 30–70% higher than most cited in literature (Young, 1960; Schwartz et al, 1961; Kovacs et al, 2003; Stormer et al, 2006), it has been reported previously and noted by Chiou (1971) that the anodization constant can vary with anodization conditions, including hold times, temperature, and electrolyte composition. It should be noted that, using dilute ammonium pentaborate, Habazaki et al (2006) recently achieved anodized films ∼340 nm thick at a potential of 100 V.…”
Section: Resultsmentioning
confidence: 61%
“…Niobium metal is much more abundant and is chemically similar to tantalum (Nb, Z = 41 and Ta, Z = 73, both are group V transition metals). Both being valve metals (Dignam, 1981), when anodized they form an amorphous pentoxide layer where the thickness is governed by the anodization constant (Nb, ∼0.5–3.0 nm/V (Young, 1960; Kovacs et al, 2003) and Ta, ∼1.6 nm/V (Young, 1960)). Since capacitance is inversely proportional to the thickness of the dielectric layer, the capacitance of a formed anode can be tailored with the anodization voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years anodic oxidation of metal surfaces has been a popular method of preparing thin film capacitors, and the techniques of anodizing various metals have been extensively investigated (1). The oxide dielectric films formed by these methods are generally in the thickness range of 200-500A and appear to have comparatively high breakdown voltages.…”
mentioning
confidence: 99%